Shank2 contributes to the apical retention and intracellular redistribution of NaPiIIa in OK cells - Dobrinskikh, Evgenia (American Physiological Society, 2013)
In renal proximal tubule (PT) cells, sodium-phosphate cotransporter IIa (NaPiIIa) is normally concentrated within the apical membrane where it reabsorbs ∼70% of luminal phosphate (Pi). NaPiIIa activity is acutely regulated by moderating its abundance within the apical membrane. Under low-Pi conditions, NaPiIIa is retained within the apical membrane. Under high-Pi conditions, NaPiIIa is retrieved from the apical membrane and trafficked to the lysosomes for degradation. The present study investigates the role of Shank2 in regulating the distribution of NaPiIIa. In opossum kidney cells, a PT cell model, knockdown of Shank2 in cells maintained in low-Pi media resulted in a marked decrease in NaPiIIa abundance. After being transferred into high-Pi media, live-cell imaging showed that mRFP-Shank2E and GFP-NaPiIIa underwent endocytosis and trafficked together through the subapical domain. Fluorescence cross-correlation spectroscopy demonstrated that GFP-NaPiIIa and mRFP-Shank2 have indistinguishable diffusion coefficients and migrated through the subapical domain in temporal synchrony. Raster image cross-correlation spectroscopy demonstrated these two proteins course through the subapical domain in temporal-spatial synchrony. In the microvilli of cells under low-Pi conditions and in the subapical domain of cells under high-Pi conditions, fluorescence lifetime imaging microscopy-Forster resonance energy transfer analysis of Cer-NaPiIIa and EYFP-Shank2E found these fluors reside within 10 nm of each other. Demonstrating a complexity of functions, in cells maintained under low-Pi conditions, Shank2 plays an essential role in the apical retention of NaPiIIa while under high-Pi conditions Shank2 remains associated with NaPiIIa and escorts NaPiIIa through the cell interior.